High-speed trains versus air transport vectors for mass transfers of critically ill patients: The TRANSCOV cohort study - Chatpimuk Thipayamaskomon; Olivier Grimaud; Pierre Tattevin; Lionel Lamhaut; Emmanuelle Leray; Noemie Letellier; Sahar Bayat; Christophe Fermanian; Sylvie Martin; Jean-Marc Philippe; Eric Maury; Marc Noizet; et al. (PLoS ONE, 2026)
Background The first COVID-19 epidemic wave hit the East and Ile-de-France regions in France, resulting in overwhelmed intensive care units (ICUs). Alongside helicopters and planes, high-speed trains were used for the first time to mass-evacuate critically ill patients. This study aimed to compare outcomes of patients evacuated by trains and by aircrafts. Methods This was a multicentre retrospective cohort study. Between 13 March and 10 April 2020, 38 ICUs in France transferred patients with severe COVID-19 to 60 ICUs in unaffected regions and countries. Patients were divided into the train group (n = 130) and the air group (n = 163). The study outcomes included 28-day case-fatality, destination ICU length of stay and post-transfer Sequential Organ Failure Assessment (SOFA) score. Results Age and comorbidity did not differ between groups. Although patients spent more time (+2 hours) and travelled further (+250 km) in the train group than in the air group, the median post-transfer SOFA score was lower in the train group (6 vs 7; p = 0.03). The 28-day mortality rates were not different (train/air unadjusted incidence risk ratio: 0.96; p = 0.94). The ICU stay duration was shorter (−6 days) in the train group, but this difference was reduced after adjusting for clinical events, such as nosocomial infections. Conclusion High-speed train was a safe vehicle for remote transfer of critically ill patients. The selection of healthier patients and the better physiological and care conditions during the evacuation may explain the shorter ICU stays of patients transferred by trains.